Revealing the deposition of macrophytes transported offshore: Evidence of their long-distance dispersal and seasonal aggregation to the deep sea - Kokubu Y; Rothäusler E; Filippi JB; Durieux EDH; Komatsu T (Nature Publishing Group, 2022)
The role of coastal macrophyte beds as a carbon sink is under debate. Various studies have provided global estimates of the carbon sequestration and stocks of macrophyte beds; however, the final fate of macrophyte debris exported from coastal beds remains uncertain, and must be determined in order to fully clarify the role of coastal vegetation as a carbon sink. Here we conducted bottom-trawl surveys to investigate the extensive and seasonal aggregation of exported macrophytes on the continental shelf and slope seafloor (40-1,800 m). Sunken macrophytes showed a clear seasonal trend with highest biomasses in summer. This was mainly caused by the most collected macrophyte species Sargassum horneri. Furthermore, we used numerical simulations to verify the link between sea-surface hydrographic condition and seafloor distribution of sunken macrophytes. Our results showed that S. horneri accumulated beneath the Kuroshio Extension current, which is the western boundary current of the North Pacific subtropical gyre. Overall, floating macrophytes that became transported offshore by a stable sea-surface current, such as the western boundary current, constitute an organic carbon pathway from coastal waters to the deep sea. Our findings suggest that these buoyant macrophytes can act as a biological pump to enhance oceanic carbon sequestration.